The complete guide to international financial reporting standards : including IAS and interpretation - Tiffin, Ralph (London : Thorogood, 2004)
A guide that explains the principles of IAS and the accounting and disclosure agreements, and clarifies practical problems of compliance. It contains chapters on: why IAS is needed; ideas and concepts; key terms; required accounting/disclosure; problem areas and questions to ask; and, objectives and further definitions.
oif 11/03/15
Loans
Keywords: Financial statements; Accounting; IFRS